Persepsi Manajer tentang Pengaruh Informasi Akuntansi terhadap Kinerja : Budaya, Ketidakpastian Lingkungan sebagai Variabel Moderating - Enny Susilowati (STIE Widya Manggala, 2010)
The research examined the effect of Accounting Information toward Managerial Performance by examining Organizational Culture and Perceived Environmental Uncertainty as a moderating variables. This research used samples of Manager of PT Shield On Services in Indonesia. The total number of the research was 75 respondents selected by using sensus methods. The data was collected by distributing questioners. From 75 questioners which were distributed, there were 44 respondents giving back and they could be processed and also analyzed. The hypothesis testing model used Partial Least Square analysis (PLS) . The result of the research showed that Accounting Information affected positively on Manager Performance. Organizational Culture affected positively on Manager Performance and its interactions. However, Perceived Environmental Uncertainty affected negatively on Manager Performance. The positive result in Organizational Culture gave the impact for PT Shield on Service to more focus to apply the Organization Culture orienting at manager especially in participative decisionmaking, manager held more responsibility to conduct every decision managerial from lower manager until top manager.